Performance of the Standard Chartered Bank Malaysia / Hazlin Abd Rahim - Abd Rahim, Hazlin (Faculty of Business and Management, 2010)
This report has been done to study the financial performance of Standard Chartered Bank Malaysia from 2005 until 2009. This study using some sources like secondary data and other approaches such as financial ratios and gap analysis has been use as a data collection. The data is taken from external sources such as journal, internet, and books of Financial Analysis. Result from this study, the standard chartered bank Malaysia has a not very well performance because of the economic downturn, external factors like political, wars, foreign exchange and oil pricing increase. From the analysis also the Standard Chartered Bank should have initiative to increase the profit of the bank. This have some summarize from standard Chartered Bank Malaysia performance. It can look in the financial performance analysis. Starting on the 2005 until 2007, the performance of the bank is not very attractive because of the economic Malaysia problem or external problem. In the 2008 the performance of bank is very well compare the others previous years. In the 2009 the Malaysia economic still in recovery, the performance of the Standard Chartered Bank is very bad because of the Standard Chartered Bank cannot collect the debt on time and very high expenses. Hopefully, this report can give valuable information about the performance of the company to their customers, creditor and other related parties.